2017
DOI: 10.1371/journal.pone.0181660
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Aspergillus frankstonensis sp. nov. during environmental sampling for animal and human fungal pathogens

Abstract: Invasive fungal infections (IFI) due to species in Aspergillus section Fumigati (ASF), including the Aspergillus viridinutans species complex (AVSC), are increasingly reported in humans and cats. The risk of exposure to these medically important fungi in Australia is unknown. Air and soil was sampled from the domiciles of pet cats diagnosed with these IFI and from a nature reserve in Frankston, Victoria, where Aspergillus viridinutans sensu stricto was discovered in 1954. Of 104 ASF species isolated, 61% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
0
15
0
3
Order By: Relevance
“…Sexual morph not observed in culture, or present, neosartorya-type, homo- or heterothallic, white, yellowish white. Series description based on Talbot et al. (2017) and Hubka et al.…”
Section: Resultsmentioning
confidence: 99%
“…Sexual morph not observed in culture, or present, neosartorya-type, homo- or heterothallic, white, yellowish white. Series description based on Talbot et al. (2017) and Hubka et al.…”
Section: Resultsmentioning
confidence: 99%
“…Fumigati . The taxonomy of AVSC has developed rapidly since eight of the currently 11 recognized species were described in the last four years (Barrs et al 2013, Eamvijarn et al 2013, Nováková et al 2014, Sugui et al 2014, Matsuzawa et al 2015, Talbot et al 2017). The species boundaries delimitation was usually based on comparison of single-gene phylogenies and principles of genealogical concordance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies supported the species concept by results of in vitro mating experiments between opposite mating type strains. With the increasing number of species, available isolates and new mating experiment data, the species boundaries in AVSC became unclear as pointed out by Talbot et al (2017) who used the designation ‘ A. felis clade’ for A. felis and related species. Importantly, Sugui et al (2014) and Talbot et al (2017) identified that interpretation of in vitro mating assays in sect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As espécies patogênicas mais frequentes que causam a aspergilose são A. fumigatus, A. flavus, A. terreus e A. niger, entretanto, espécies crípticas e raras também estão sendo identificadas em pacientes imunocompetentes e imunocomprometidos, incluindo membros do complexo de espécies de Aspergillus viridinutans (GUPTA et al, 2015;MASIH et al, 2016;TALBOT et al, 2017).…”
Section: Introductionunclassified